Designing New‐Generation Piezoelectric Transducers by Embedding Superior Graphene‐Based Thermal Regulators. Issue 41 (27th August 2021) - Shan, Junjie; Wang, Sha; Zhou, Fan; Hu, Jingyi; Liu, Qingqing; Lin, Shuyu; Zhang, Yanfeng; Liu, Zhongfan
Abstract: Cascaded‐piezoelectric‐transducers (CPETs) is a key component in modern energy‐conversion fields, possessing versatile applications in ultrasonic scalpels, acoustic levitation, and sonar. However, serious self‐heating inevitably occurs inside high‐power CPETs, severely limiting their practical applications in broader fields. To tackle this, multidirectional heat‐escape channels of multidimensional (multi‐D, 3D/2D) graphene films are introduced in designing new‐type thermal regulators. A porous AlN‐ceramic thermal‐sink is creatively selected as a template for directly synthesizing graphene via a two‐step chemical vapor deposition strategy. This perfect combination of 3D/2D‐graphene and the AlN ceramic can integrate their complementary advantages in uniformizing, transmitting, and releasing heat. Amazingly, in the new‐generation CPETs embedded with these graphene‐based thermal regulators, the self‐heating‐induced temperature rise can be substantially reduced by ≈60% (far exceeding actual demand standard). As another kernel parameter, electroacoustic‐energy‐conversion efficiency is dramatically improved in the new‐generation CPETs. Briefly, this research realizes the first synthesis of a novel multi‐D‐graphene/AlN‐ceramic hybrid, and propels its brand‐new application directions in new‐generation energy‐conversion‐ and thermal‐management‐related territories. Abstract : Efficient multidirectional heat‐escape channels are constructed via synthesizing a brand‐new chemical‐vapor‐deposition‐derived 3D/2D graphene homojunction on an AlN‐thermosensitive‐ceramic template. New‐generation cascaded‐piezoelectric‐transducers are designed and constructed via embedding the 3D/2D‐graphene/AlN‐ceramic‐based thermal regulators, which can simultaneously uniformize, transmit, and release heat. The self‐heating‐caused temperature rise is substantially reduced by ≈60%, along with dramatically enhanced electroacoustic‐energy‐conversion efficiency and amplitude.